Pengaruh Total Quality Management Terhadap Kinerja Manajerial (studi empiris di Perusahaan Daerah Pasar Surya) - Kurniawan Tricahyo Pamungkas (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2015)
Abstractquality management is often used as measurement tool in assessing managerial performance. However, the results of several reseacrhshowed inconsistencies. This happens because not all companies are able to implement total quality management well. This research was conducted in PD. Pasar Surya (Local Government Company of market Town of Surabaya). Data obtained through questionnaries distributed to lower level managers to top level managers. The data was analyzed from totaled 39 questionnaries. The analysis technique used is a simple regression. The result of this research showed that the total quality management has a significant positive effect on managerial performance.